(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Vegetable oil has been investigated to displace products which are derived frompetroleum because of its environmentally-safe properties and has become a vital source forbio-lubricants. Vegetable oil availability as one of the renewable sources is one of theusefulness of it. Additionally, the vegetable oils based lubricant has indicated the potentialsfor reducing carbon dioxide and hydrocarbon emission while operating in internalcombustion engines and in industrial processes. In this study, the mustard seeds oil wasinvestigated to study its lubricant characteristics under different loads while comparing itwith commercial lubricant using a pin-on-disk tribometer. The whole experiential workswere corresponding to American Society for Testing and Materials (ASTM G99).Under lowload, the results exhibit that the mustard seeds oil shows adequate tribological characteristicscompared to other petroleum oil samples. In conclusion, the mustard seeds oil has a betterwear and friction resistance. Therefore, mustard seeds oil can be used for lubrication ofmating components.